Inflammation and Severe Cerebral Venous Thrombosis - Hu, Shuyuan; Lee, Hangil; Zhao, Haiping; Ding, Yuchuan; Duan, Jiangang (Frontiers in Neurology, 2022)
Cerebral venous thrombosis (CVT) is a rare type of venous thromboembolism (VTE). It is an important cause of stroke in young adults and children. Severe CVT, which is characterized by cerebral venous infarction or hemorrhage, seizures, or disturbance of consciousness, has more severe clinical manifestations and a worse prognosis. It is commonly believed that the onset of severe CVT gave credit to venous return disorder, with the underlying pathogenesis remaining unclear. There is increasing evidence suggesting that an inflammatory response is closely associated with the pathophysiology of severe CVT. Preclinical studies have identified the components of neuroinflammation, including microglia, astrocytes, and neutrophils. After CVT occurrence, microglia are activated and secrete cytokines (e.g., interleukin-1β and tumor necrosis factor-α), which results in a series of brain injuries, including blood-brain barrier disruption, brain edema, and cerebral venous infarction. Additionally, astrocytes are activated at the initial CVT stage and may interact with microglia to exacerbate the inflammatory response. The extent of cerebral edema and neutrophil recruitment increases temporally in the acute phase. Further, there are also changes in the morphology of inflammatory cells, expression of inflammatory mediators, and inflammatory pathway molecules with CVT progression. Lately, some clinical research suggested that some inflammation-related biomarkers are of great value in assessing the course, severity, and prognosis of severe CVT. Moreover, basic and clinical researches suggested that anti-inflammatory therapy might hold promising in severe CVT. This study reviews the current literature regarding the involvement of inflammation in the pathophysiology and anti-inflammatory interventions of severe CVT, which would contribute to informing the pathophysiology mechanism and laying a foundation for exploring novel severe CVT therapeutic strategies.